PENGARUH KOMPETENSI PEGAWAI TERHADAP PRODUKTIVITAS KERJA PEGAWAI DINAS KESEHATAN KOTA BANDUNG - Rodlial Ramdhan Tackbir Abubakar (Jurnal Administrasi Negara, 2018)
This research aims to understand the effect of the Bandung Health Office employee competency on their productivity. The research uses quantitative method, particularly path analysis, which reveals the scale of effect of employee competency on productivity, both simultaneously and partially. The result showcases that simultaneously, the effect of employee competency (X) on productivity (Y) is 68.9%, while the effect of other factors (Îµ) on productivity (Y) is 31.1%. Partially, the influence of employee competency (X) consists of three main components those are attitude (X1) which has positive effect on productivity (Y) by 17%, knowledge (X1) which has positive effect by 42.1%, and skills (X3) which has positive effect by 9.8%. From the three competency components which have partial positive effect on productivity, it can be seen that knowledge (X1) is the dominant partial factor in determining the productivity of Bandung Health Office employees. A conclusion drawn in this research is that employee competency has positive effect on productivity of Bandung Health Office employees. Moreover, the three components of competency which affect productivity have been applied comprehensively.